Merger Review Process Finance PT Timah (Persero) Tbk and PT Tambang Timah - Eliani, Fina; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
Law no 4 in 2009 is about Mineral and Coal Mining 2009 and its implementation rules set mining companies do their own mining activities and conduct processing and refining facilities in the country and has its own processing or purification. PT. Timah (Persero) Tbk is having the biggest Tin Mining Permit in Indonesia but has no mining equipment, metal processing and refining facilities and other assets due to the mining operations supporting the asset has been transferred in the context of business expansion (spinn off) in 1998 as a capital contribution Subsidiary to the PT.Tambang Timah. After the enactment of the Mining Law, PT. Timah Tbk conduct mining activities that give rise to its own internal transactions between PT. Tambang Timah and PT. Timah Tbk ineffective and inefficient.In 2012 Minister of Energy and Mineral Resources (ESDM) published law No.7/2012 of Added Value Through Mineral Processing and Refining Mineral activities, in order to comply with the regulations PT. Timah Tbk purchase processing facilities and / purification along with other supporting assets are located in Unit Metallurgy. Therefore it will be proposed merger solution. Analysis shows that with merger in 2013 reachs efficiency Rp. 8.9 billion and increase in cash / cash equivalents of Rp 23, 7 billion. Expected merger synergies will also result in managerial, streamlining organizational structure and company’s support going concern. Through this merger would make PT. Timah Tbk as mining companies an efficient and integrated with core ownership of whole mining assets so it can achieve the conditions in accordance with the Mining Law and its implementation. Keywords: Mining Law, Merger (Merger), PT. Timah Tbk, PT. Tambang Timah